2023
DOI: 10.11141/ia.64.14
|View full text |Cite
|
Sign up to set email alerts
|

Getting it Together: Combining information about archaeological sites and artefacts in ARIADNE

Julian D. Richards

Abstract: This article discusses the situation that exists in several European countries, whereby information about archaeological sites and monuments, and that about finds recorded by members of the public (primarily via metal detecting), is held in entirely separate databases. This prevents heritage management decisions being taken with full awareness of known archaeology, and makes research that seeks to draw on multiple information resources difficult. The article demonstrates how the European ARIADNE e-infrastructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It is essential to note, however, that the role of the ARIADNE aggregation service is not to duplicate services already available from data providers' own web sites, but rather to provide interoperability and resource discovery across multiple resources. Nonetheless in some cases the portal provides a powerful research tool in its own right (Richards 2023). The service was built upon the foundations laid by a number of preceding projects but further lessons have been learnt.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to note, however, that the role of the ARIADNE aggregation service is not to duplicate services already available from data providers' own web sites, but rather to provide interoperability and resource discovery across multiple resources. Nonetheless in some cases the portal provides a powerful research tool in its own right (Richards 2023). The service was built upon the foundations laid by a number of preceding projects but further lessons have been learnt.…”
Section: Discussionmentioning
confidence: 99%
“…Use of different search filters allows new types of research, for example, to explore and compare patterns of sites and artefacts found in different regions and relating to different cultural periods. Richards (2023b) presents examples for this research capability regarding artefacts. It was not possible to achieve such research so effectively before.…”
Section: The Portal As An Effective Research Tool Also Including Cont...mentioning
confidence: 99%
“…Smaller repositories, in particular, face difficulties with interoperability and sustainability. As a result, standardizing practices and fostering collaborations are crucial for integrating these repositories into the global research community (Bibby, 2021;Bisták et al, 2021;Calandra et al, 2021;Correia & Silva, 2023;Faniel et al, 2018;Geser et al, 2022;Göldner et al, 2023;Huvila, 2020;Jantos & Sommer, 2021;Juty et al, 2020;Kansa et al, 2020;Kreiter, 2021;Nicholson et al, 2023;Novák et al, 2021;Oniszczuk & Makowska, 2021;Richards, 2021Richards, , 2023bRichards, , 2023aRichards et al, 2021;Seaton et al, 2023;Štular, 2021;Trognitz, 2021;Wallis et al, 2013;Wilkinson et al, 2016).…”
mentioning
confidence: 99%